Thought leadership profile of NTU student leaders. - Lim, Deborah Yi Ling. (2008)
Our research paper is based on the holistic leadership model known as Thought Leadership Model. We attempt to draw a linkage between LIQ level (proxy for Thought Leadership level), and the attributes of Thought Leadership and demographics of student leaders in NTU, based on a sample size of 258 respondents.